Supraglottic Kaposi’s Sarcoma in HIV-Negative Patients: Case Report and Literature Review - Ela A. Server; Yusuf M. Durna; Ozgur Yigit; Erol R. Bozkurt (Case Reports in Otolaryngology, 2016)
This paper presents a case report of an HIV-negative, supraglottic Kaposi’s sarcoma patient. The 80-year-old male patient was admitted with complaints of hoarseness, difficulty in swallowing, and a stinging sensation in his throat for approximately six months. The endoscopic larynx examination revealed a lesion which had completely infiltrated the epiglottis, reached right aryepiglottic fold, was vegetating, pink and purple in color, multilobular, fragile, and shaped like a bunch of grapes, and partially blocked the bleeding airway passage. The case was discussed by the hospital’s head-neck cancer committee and a surgery decision was made. A tracheotomy was performed under local anesthesia before the operation due to respiratory distress and endotracheal intubation difficulty. Direct laryngoscopy showed that the mass was limited in the supraglottic area, had invaded the entire left aryepiglottic fold and one-third of the front right aryepiglottic fold, and completely covered epiglottis. It should be remembered that although rare, Kaposi’s sarcoma may be encountered in larynx malignancy cases. Disease-free survival may be achieved through local excision and postoperative radiotherapy.